2004
DOI: 10.1097/00004872-200409000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of 24-h ambulatory blood pressure characteristics for cardiovascular morbidity in a population of elderly men

Abstract: Ambulatory PP was a powerful predictor of CV morbidity in elderly men, independently of office PP and other established cardiovascular risk factors. Moreover, variability of daytime SBP added important prognostic information, suggesting that 24-h ambulatory BP monitoring may contribute to an improved risk assessment in elderly subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 29 publications
2
113
0
1
Order By: Relevance
“…By contrast, Hansen et al 17 observed that the night-day BP ratio was significant for CVD events in subjects with elevated daytime ABP, but not in subjects with normal daytime ABP, and these results persisted after adjustment for 24-h ABP. Finally, the night-day BP ratio did not carry any prognostic information in the study by Bjö rklund et al 20 in a population of elderly men.…”
Section: Discussionmentioning
confidence: 66%
“…By contrast, Hansen et al 17 observed that the night-day BP ratio was significant for CVD events in subjects with elevated daytime ABP, but not in subjects with normal daytime ABP, and these results persisted after adjustment for 24-h ABP. Finally, the night-day BP ratio did not carry any prognostic information in the study by Bjö rklund et al 20 in a population of elderly men.…”
Section: Discussionmentioning
confidence: 66%
“…Possible limitations of previous studies were a lack of statistical power, 2-5 selection of specific groups of patients, [5][6][7] categorization of variability by arbitrary cutoff points, 2,4,[7][8][9] and sole reliance on fatal end points. 10,11 Moreover, various parameters can capture short-term blood pressure variability over 24 hours, but most studies only considered the SD of systolic 4,6,12 or diastolic blood pressure or both. 8 -10 To address the prognostic value of short-term blood pressure variability, we expanded, updated, and analyzed the International Database on Ambulatory Blood Pressure in Relation to Cardiovascular Outcome.…”
mentioning
confidence: 99%
“…On the contrary, the night-to-day ratio of systolic and diastolic BP was not associated with CV morbidity in this cohort, irrespective of the cutoff value used for the definition of nondipping. 42 These results diverge greatly from the findings of the Systolic Hypertension in Europe (Syst-Eur) study 43 and the PIUMA (Progetto Ipertensione Umbria Monitoraggio Ambulatoriale) study, 44 in which the nondipping BP pattern was a predictor of CV morbidity.…”
Section: Elderlymentioning
confidence: 85%